EXPLORING LANGUAGE ATTITUDES AND IDENTITY CONSTRUCTION IN ARABIC DIGLOSSIA - Ahmed, Ohod Faisal (Translation and Linguistics (Transling), 2024)
This research explores the complex field of Arabic diglossia, with a particular emphasis on how language attitudes and identity formation are constructed within this framework. The research includes 26 native Arabic speakers who are studying in Indonesia, with a focus on both high (Modern Standard Arabic, MSA) and low (regional dialects) types. This study use descriptive qualitative study explores the intricate sociolinguistic dynamics of Arabic diglossia by examining the perspectives of Arabic speakers. Participants, proficient in both Modern Standard Arabic (MSA) and regional dialects, revealed a prevailing positive attitude toward MSA, particularly in formal and academic contexts, underlining its perceived prestige associated with intellectual discourse, cultural preservation, and historical continuity. Contrasting attitudes toward regional dialects emerged, ranging from strong attachments to pragmatic views, underscoring the complexity of individual language attitudes. Contextual appropriateness played a crucial role in language choices, with MSA favoured in formal settings and regional dialects in informal interactions. The study unravelled the interplay between language choices and identity, highlighting varied degrees of identification with pan-Arab and local/regional identities. Zoom Meetings shed light on the difficulties in switching between MSA and regional languages and offered insights into diglossia competency. Sociocultural adaptations demonstrated how language can be flexible in response to a range of situations. This study emphasizes the intricacies of linguistic attitudes, identity development, and adaptive language usage in multilingual environments, adding nuanced views to our knowledge of Arabic diglossia